Feasibility of Using Bioelectrochemical Systems for Bioremediation - Jin, S.; Fallgren, P.H.
Bioelectrochemical systems (BESs)are a category of biologically based technologies that combine biological, primarily microbial and enzymatic, pathways with electrochemical enhancement to complete biochemical reactions and generate energy or chemical products. This chapter focuses on the application of one type of BES, the microbial fuel cell, for bioremediation. Different types of BES have been investigated in bioremediation applications for a wide range of environmental contaminants. BES is composed of anodes and cathodes, and different reactions occur at each electrode type, which can be applied to remediation. Oxidation processes (e.g., hydrocarbons and other contaminants of lower oxidizing potentials)can occur at the anode, while reduction processes (e.g., chlorinated hydrocarbons and other contaminants of higher oxidizing potentials)occur at the cathode. Based on results from laboratory and field-scale studies, BES demonstrates its feasibility and emerges as a novel and sustainable remediation technology. © 2014 Elsevier Inc. All rights reserved.
Keywords: BES; BIOELECTROCHEMICAL SYSTEM; BIOREMEDIATION; MFC; MICROBIAL FUEL CELL